Defining Porphyromonas gingivalis strains associated with periodontal disease - Vijaya Murugaiyan; Simran Utreja; Kathleen M. Hovey; Yijun Sun; Michael J. LaMonte; Jean Wactawski‑Wende; Patricia I. Diaz; Michael J. Buck (Scientific Reports, 2024)
Abstract Porphyromonas gingivalis, a Gram-negative anaerobic bacterium commonly found in human subgingival plaque, is a major etiologic agent for periodontitis and has been associated with multiple systemic pathologies. Many P. gingivalis strains have been identified and different strains possess different virulence factors. Current oral microbiome approaches (16S or shotgun) have been unable to differentiate P. gingivalis strains. This study presents a new approach that aims to improve the accuracy of strain identification, using a detection method based on sequencing of the intergenic spacer region (ISR) which is variable between P. gingivalis strains. Our approach uses two-step PCR to amplify only the P. gingivalis ISR region. Samples are then sequenced with an Illumina sequencer and mapped to specific strains. Our approach was validated by examining subgingival plaque from 153 participants with and without periodontal disease. We identified the avirulent strain ATCC33277/381 as the most abundant strain across all sample types. The W83/W50 strain was significantly enriched in periodontitis, with 13% of participants harboring that strain. Overall, this approach can have significant implications not only for the diagnosis and treatment of periodontal disease but also for other diseases where P. gingivalis or its toxins have been implicated, such as Alzheimer's disease.